Medical E-Consultation System (MECS) - Shdefat, Ahmed Younes Khairo (2010)
This study aims at establishing a medical consultation system using web-based tools such as PHP and MYSQL. The development of the system will be associated with the linking the website to a knowledge base rather than an ordinary database, using some popular framework like MYSQL. In addition, some expert system techniques are included through the application of intelligent database terms during the matching process of the symptoms provided by users. Features of the system include providing survey-based online diagnoses for patients, such as that produced by doctors. Furthermore, the system will provide information about various diseases, presenting them in the format of online materials. Moreover, it will also provide an online forum where specialists, trainees and patients can interact with each other using questions-answers information sharing technique. On the other hand, users of the system will be able to take advantage of online system-access. Consequently, the system will be meeting the user needs through better understanding of system requirements from the developers' perspectives according to the user needs in the correct and proper way.